Pengaruh Penetapan Harga dan Kualitas Layanan Terhadap Intention To Purchase : (Studi Kasus Pada Pelabuhan Bandar Bakau Jaya Kabupaten Lampung Selatan) - Arseta Yudha Lesmana; Andala Rama Putra Barusman; Tina MB Virgawenda (Jurnal Ilmiah ESAI, 2020)
The port is one of the drivers of the economy because it is the main gateway in the process of up and down passengers, as well as a facility that facilitates the distribution of production and trade between islands. The port becomes a public facility where interactions between users are established in connection with economic activity. The purpose of this study is to find out how much the influence of pricing and service quality on the intention to purchase at port services companies and ferry crossings in South Lampung. This research was conducted by disseminating questionnaires to port service users and data analysis methods using multiple linear regressions. The results showed that pricing has a positive and significant effect on intention to purchase and the quality of service has a positive and significant effect on intention to purchase.